Nanocellulose Composites as Smart Devices With Chassis, Light-Directed DNA Storage, Engineered Electronic Properties, and Chip Integration - Bencurova, Elena; Shityakov, Sergey; Schaack, Dominik; Kaltdorf, Martin; Sarukhanyan, Edita; Hilgarth, Alexander; Rath, Christin; Montenegro, Sergio; Roth, Günter; Lopez, Daniel; Dandekar, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
The rapid development of green and sustainable materials opens up new possibilities in the field of applied research. Such materials include nanocellulose composites that can integrate many components into composites and provide a good chassis for smart devices. In our paper, we evaluate four approaches for turning a nanocellulose composite into an information storage or processing device: (i) Nanocellulose can be a suitable carrier material and protect information stored in DNA. (ii) Nucleotide-processing enzymes (polymerase, exonuclease) can be controlled by light after fusing them to light-gating domains; nucleotide substrate specificity can be changed by mutation or pH change (read-in and read-out of the information). (iii) Semiconductors and electronic capabilities can be achieved: we show that nanocellulose is rendered electronic by iodine treatment replacing silicon including microstructures. Nanocellulose semiconductor properties are measured and the resulting potential including single-electron transistors (SET) and their properties are modelled. Electric current can also be transported by DNA through G-quadruplex DNA molecules; these as well as classical silicon semiconductors can easily be integrated into the nanocellulose composite. (iv) To elaborate upon miniaturization and integration for a smart nanocellulose chip device we demonstrate pH-sensitive dyes in nanocellulose, nanopore creation and kinase micropatterning on bacterial membranes as well as digital PCR micro-wells. Future application potential includes nano-3D printing, fast molecular processors (e.g. SETs) integrated with DNA storage and conventional electronics. This would also lead to environmental-friendly nanocellulose chips for information processing as well as smart nanocellulose composites for biomedical applications and nano-factories.